The Increased Cardiovascular Risk in Patients Affected by Autoimmune Diseases: Review of the Various Manifestations - Durante, Alessandro (J Clin Med Res, 2015)
Cardiovascular and autoimmune diseases are among major health concerns in developed countries, and both represent a significant source of morbidity, mortality and economic costs. Despite they are thought to affect subjects at different ages, most of the deaths of patients affected by autoimmune diseases are represented by cardiovascular deaths. Several manifestations of cardiovascular diseases can be observed in patients with autoimmune diseases, such as endothelial dysfunction, accelerated atherosclerosis and an increase in the rate of acute coronary syndromes. Thus, people with autoimmune diseases have an increased cardiovascular risk and a worse outcome in the case of cardiovascular events. In this review, we will describe the correlations between the two spectra of diseases.